Exploring Teachers' Awareness of Transformative Learning and Its Impact on Teaching Practices - Mulyadi, Dadi; Amelia, Della; Emilzoli, Mario; Nurrohman, Mohammad Nazwan; Firly, Shabran Ghazi Nabil (Universitas Pendidikan Ganesha, 2024)
The lack of teachers' understanding of transformative learning principles poses a major challenge in fostering innovative, student-centered learning. This study aims to compare teachers' levels of understanding of transformative learning principles across specific categories and examine the correlation between their understanding and teaching practices. The study employs a quantitative approach with exploratory descriptive and correlational methods. The sample consisted of 103 junior and senior high school teachers, randomly selected, comprising 50 females and 53 males. Data were collected through an online survey using a structured questionnaire with 46 questions. Data analysis was conducted using descriptive and inferential statistical techniques. The results revealed that the majority of teachers demonstrated low to moderate levels of understanding of transformative learning principles. Teachers with greater understanding tended to implement transformative approaches more frequently in their teaching practices. However, no significant differences were found based on gender, age group, or teaching experience. The study concludes that intensive and continuous professional development programs are needed to enhance teachers' understanding and skills in applying transformative learning. These programs should include conceptual training, reflective practices, and collaborative support to facilitate classroom implementation.